Induction of Variegata Red Majesty Using EMS Mutagen and Gibberellins in Vitro - Indrayanti, Shelfina; Sudirman, S.; Sabaria, S.; Basri, Anisa Luthfia (Universitas Sembilanbelas November Kolaka, 2023)
This study aims to determine how the interaction occurs between the best concentration of EMS with gibberellin in inducing aglaonema variegata and regeneration of aglaonema Red Majesty in vitro. The research was conducted at the Tissue Culture Laboratory of the Faculty of Agriculture, Hasanuddin University and took place from January to June 2022. The study used the method of Separate Plots Design in a Completely Randomized Design as the environmental design. The results showed that the best mutant genetic diversity and in vitro regeneration at 0.3 percent EMS concentration with 15 ppm gibberellin (variegata), and 45 ppm (chimera) and 0.6 percent EMS concentration with 0 ppm gibberellin (variegata) had different characters compared to the control treatment and other treatments